Information technology project management - Schwalbe, Kathy (Australia United States Cengage, 2019)
"Introduce exciting opportunities and challenges in technology with Schwalbe's INFORMATION TECHNOLOGY PROJECT MANAGEMENT, 8E. This unique book demonstrates principles distinctive to managing information technology (IT). No book offers more insights and software tools for IT project management success, including updates that reflect the latest PMBOK® Guide, 5E. This edition weaves theory with successful practices for an integrated focus on the concepts, tools, and techniques that are most effective today. This is the only text to apply all 10 project management knowledge areas to IT projects. Students master skills in project integration, scope, time, cost, quality, human resource, communications, risk, procurement, and stakeholder management as well as all five process groups -- initiating, planning, executing, monitoring and controlling, and closing. Intriguing examples, MindView software, and a guide to Microsoft® Project 2013 help students refine their marketable skills." -- Publisher's website.
Keywords: Project management; Information technology -- Management; Information technology projects -- Management